Relatório do estágio curricular supervisionado em Medicina Veterinária - área de bovinocultura de leite - (:unkn) unknown (Universidade Federal do Pampa, 2018)
This report describes the main activities monitored and developed during the Supervised Curricular Internship in Veterinary Medicine (ECSMV) carried out in the area of dairy cattle. The place chosen was the Pioneiros Veterinary Polyclinic, located in the municipality of Carambeí - Paraná, under the supervision of veterinarian Edomar Kiefer and guidance from veterinary doctor Profa. Dr. Mirela Noro. During the internship, It is possible to follow several activities related to the company's routine, highlighting attendance at the medical clinic and surgical clinic, sanitary, reproductive and productive management of the animals, thus contemplating all the managements that involve dairy cattle. This report presents the main activities monitored and discusses critical points for the welfare and productivity of the dairy cow, seen in different commercial properties in the region of the general fields of Paraná. The internship provided great personal and professional learning, as well as the acquisition of a critical and constructive vision within the dairy cattle production systems. The internship took place from January 10 to April 4, 2018, for a total of 472 hours.
Report of the supervised curricular internship in Veterinary Medicine - area of dairy cattle
Keywords: Gado leiteiro; Bovinocultura leiteira; Clínica de grandes animais; Bovinos; Dairy cattle; Large animal clinic; Dairy Cattle; Cattle; Medicina Veterinária; Reprodução animal; Animal reproduction; CNPQ::CIENCIAS AGRARIAS